2021
DOI: 10.1186/s13063-021-05031-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of immersive virtual reality technology on gait rehabilitation in stroke patients: a study protocol for a randomized controlled trial

Abstract: Background The high incidence of cerebral apoplexy makes it one of the most important causes of adult disability. Gait disorder is one of the hallmark symptoms in the sequelae of cerebral apoplexy. The recovery of walking ability is critical for improving patients’ quality of life. Innovative virtual reality technology has been widely used in post-stroke rehabilitation, whose effectiveness and safety have been widely verified. To date, however, there are few studies evaluating the effect of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
(7 reference statements)
0
18
0
Order By: Relevance
“…Studies have shown that rehabilitation training supported by virtual reality is beneficial to task training, multisensory feedback, diversified rehabilitation tasks, and patients' enthusiasm [10]. Cai et al outlined the application of immersive virtual reality assisted rehabilitation technology in stroke patients' gait rehabilitation and compared it with traditional rehabilitation methods [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that rehabilitation training supported by virtual reality is beneficial to task training, multisensory feedback, diversified rehabilitation tasks, and patients' enthusiasm [10]. Cai et al outlined the application of immersive virtual reality assisted rehabilitation technology in stroke patients' gait rehabilitation and compared it with traditional rehabilitation methods [11].…”
Section: Introductionmentioning
confidence: 99%
“…2) Security. In order to show how dangerous these or other situations are, we cannot subject students to certain tests, such as a fire or various kinds of natural disasters, and how to deal with them [4]. But with the use of virtual reality, it is possible for students to perform heart surgery, to control various techniques, for example, by train, to go on a space journey and even enter the Earth's orbit [5].…”
Section: Resultsmentioning
confidence: 99%
“…More recent reviews by Canning et al ( 2020 ), Huygelier et al ( 2021 ), and Keshner and Lamontagne ( 2021 ) highlighted the concrete contributions of VR to rehabilitation of balance and gait; suggesting that the most promising effects of VR are the ability to multitask in a VE that can replicate the demands of a physical space. There is indeed already a promising body of evidence for effective virtual walking techniques in populations such as stroke (Mirelman et al, 2010 ; Cai et al, 2021 ), multiple sclerosis (Samaraweera et al, 2013 ; Winter et al, 2021 ), Parkinson's disease (Janeh et al, 2019a ; Quek et al, 2021 ), and Alzheimer's disease (White and Moussavi, 2016 ). In this section, we summarize the different VR-based gait rehabilitation approaches:…”
Section: Virtual Walking Techniques For Gait Rehabilitationmentioning
confidence: 99%
“…Other researchers have used new technologies of locomotion devices, such as Strider (Freiwald et al, 2020 ), 360° VR video-based immersive cycling training system (Lee et al, 2021 ) and KatWalk omnidirectional treadmill (Cherni et al, 2021 ). In addition, a recent study by Cai et al ( 2021 ) has shown that WIP is feasible on gait rehabilitation of stroke patients, which translates the viewpoint when the user marches in a stationary location.…”
Section: Introductionmentioning
confidence: 99%